End-of-life care in Toronto neonatal intensive care units: challenges for physician trainees. Issue 6 (30th July 2013) - El Sayed, Manal F; Chan, Melissa; McAllister, Mary; Hellmann, Jonathan
Abstract : Background: Physician trainees in neonatology can find it extremely challenging to care for patients from diverse linguistic and multicultural backgrounds. This challenge is particularly highlighted when difficult and ethically challenging end-of-life (EOL) decision-making with parents is required. While these interactions are an opportunity for growth and learning, they also have the potential to lead to misunderstanding and uncertainty and can add to trainees' insecurity, unpreparedness and stress when participating in such interactions. Objectives: To explore the challenges for trainees when EOL decisions are undertaken and to encourage them to reflect on how they might influence such decision-making. Design and interview: An in-depth, semi-structured interview guide was developed: the interview questions address trainees' beliefs, attitudes, preferences and expectations regarding discussions of EOL neonatal care. Twelve interviews were completed and the audio records transcribed verbatim, after removal of identifying personal information. Results: Participants identified six domains of challenge in EOL care: withdrawal of life-sustaining treatment based on poor outcome, explaining 'no resuscitation options' to parents, clarifying 'do not resuscitate (DNR)' orders, empowering families with knowledge and shared decision-making, dealing with different cultures and managing personal internal conflict. Participants experienced the most difficulty during the initial stages of training and eventually reported good knowledge of the EOL care process. They had a sense of security and confidence working within a multidisciplinary care team, which includes experienced nursing staff as well as bereavement and palliative care coordinator within the neonatal intensive care unit. Conclusions: The challenges experienced by physician trainees when providing EOL care can serve as focal points for improving EOL educational programmes for neonatal fellowship training.